Non-small cell lung cancer and the tumor microenvironment: making headway from targeted therapies to advanced immunotherapy - De Lucia, Anna; Mazzotti, Lucia; Gaimari, Anna; Zurlo, Matteo; Maltoni, Roberta; Cerchione, Claudio; Bravaccini, Sara; Delmonte, Angelo; Crinò, Lucio; Borges de Souza, Patricia; Pasini, Luigi; Nicolini, Fabio; et al. (Frontiers in Immunology, 2025)
Over the past decades, significant progress has been made in the understanding of non-small cell lung cancer (NSCLC) biology and tumor progression mechanisms, resulting in the development of novel strategies for early detection and wide-ranging care approaches. Since their introduction, over 20 years ago, targeted therapies with tyrosine kinase inhibitors (TKIs) have revolutionized the treatment landscape for NSCLC. Nowadays, targeted therapies remain the gold standard for many patients, but still they suffer from many adverse effects, including unexpected toxicity and intrinsic acquired resistance mutations, which lead to relapse. The adoption of immune checkpoint inhibitors (ICIs) in 2015, has offered exceptional survival benefits for patients without targetable alterations. Despite this notable progress, challenges remain, as not all patients respond favorably to ICIs, and resistance to therapy can develop over time. A crucial factor influencing clinical response to immunotherapy is the tumor microenvironment (TME). The TME is pivotal in orchestrating the interactions between neoplastic cells and the immune system, influencing tumor growth and treatment outcomes. In this review, we discuss how the understanding of this intricate relationship is crucial for the success of immunotherapy and survey the current state of immunotherapy intervention, with a focus on forthcoming and promising chimeric antigen receptor (CAR) T cell therapies in NSCLC. The TME sets major obstacles for CAR-T therapies, creating conditions that suppress the immune response, inducing T cell exhaustion. To enhance treatment efficacy, specific efforts associated with CAR-T cell therapy in NSCLC, should definitely focus TME-related immunosuppression and antigen escape mechanisms, by combining CAR-T cells with immune checkpoint blockades.